Design and development of low-cost friction stir welding - Zakaria, Ahmad Syazni (2015)
The purpose of this study is to design and develop a friction stir welding (FSW) based on current CNC machine. The development is based on CNC milling machine using FSW tool that been machined. Aluminium Alloy 5083 was used as workpiece sample while mild steel was selected as the material for the tool. The experiments are based on selected welding conditions such as feed speed, tool rotation speed, plunge depth and tool design. Some of the parameter was set to a certain value, thus leaving 3 parameters with different value. For analyzation, feed speed and tool rotation was concentrated to study which parameter is the best based on analysis, either the combination of 10, 15 and 20 mm/min feed speed and tool rotation of 1000, 1500 and 2000 rpm. Post analysis involving hardness test, impact test and microstructure analysis. The experimental results were statistically analyzed to study the influence of both parameters on weld area cross section. Based on hardness test and impact test, the weld area are strong enough after combining two aluminum. The microstructural imaging shows that at certain number of feed speed or rotation speed, the weld area starting to crack. The outcome of this study shows that feed speed and tool rotation speed have significance effects on the strength and cosmetic of weld area and the best condition is at 10 mm/min feed speed and 1000 rpm of tool rotation speed. The results also shows that the setting of the experiment can have bigger effect on the welding result.